Do youth soccer players with different tactical behaviour also perform differently in decision-making and visual search strategies? - de Assis, J. V.; González-Víllora, S.; Clemente, F. M.; Cardoso, F.; Teoldo, I. (International Journal of Performance Analysis in Sport, 2020)
The study aimed to compare the decision-making and visual search strategies of young soccer players between two groups based on the results on-field specific tactical test. Ninety youth male soccer players (14.0 ± 1.06 years) affiliated to regional Brazilian clubs participated in this study (U-15 years). The tactical behaviour was assessed using the FUT-SAT assessment tool and players were grouped into two groups of tactical skill level: more skilled and less skilled. Video-based tests were used to assess decision-making, while visual search strategies were performed using the Mobile Eye-XG®. The results indicated that the more skilled showed better decision-making scores compared to the less skilled (p= 0.035. d= 0.57). The more skilled also performed a higher mean number of fixations per trial (p= 0.002; d= 0.99); and had a lower mean duration of fixation (p= 0.020; d= 0.73). No differences were found between groups in terms the percentage viewing time per locations. The results suggest that young soccer players who are more tactically skilled were also those with better decision-making and performed visual search strategies with more visual fixations of shorter duration in comparison to less skilled.